PELAKSANAAN PEMERIKSAAN SAKSI YANG TIDAK DAPAT DI DENGAR KETERANGANNYA MENURUT PASAL 168 KUHAP DALAM SIDANG DI PENGADILAN NEGERI PEKANBARU - Andre Bonar Pardede; Evi Deliana; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Based on Article 183 of the Criminal Procedure Code, The Judge has animportant role in a trial process, namely making a decision in a case byconsidering all available evidence. The system of proof in Indonesia whichadheres to the belief of judges based on at least two legitimate evidences, still hasweaknesses. Witness testimony is one of evidences in a court case in the form of awitness statement regarding a criminal event he heard and experienced byhimself, in accordance with the provisions of Article 1 point 27 of the CriminalProcedure Code. In Article 168 of The Criminal Procedure Code it is explainedthat there are several characteristic of witnesses whose testimony cannot beheard. But in cases of criminal acts as decided in the decision of the PekanbaruDistrict Court Number: 24/Pid.Pra/2017/PN.PBR, Number: 08/Pid.Pra/2017/PN.PBR, the judge presents a witness who cannot be heard or the witness has afamily relationship with the defendant.The purpose of this thesis is: First, to find out the examination of witnessesthat cannot be heard according to Article 168 of the Criminal Procedure Code inthe process of verification at Pekanbaru District Court. Second, to find out thelegal reasons for the judges in using witnesses whose testinomy cannot be heardaccording to Article 168 of the Criminal Procedure Code in the process ofverification in Pekanbaru District Court.This type of research is sociological legal research. From the results ofthe problem research there are two main things that are concluded. First, incarrying out the examination of witness statements that cannot be heard can bemade or there is an exception if it is expressly approved by the public prosecutorand the defendant. Secondly, the legal reason for the judge to use the testimonycannot be heard because of a criminal offense committed in the family sphere.Keywords: Proof – Family Witness – Judge’s Perception